Compatibility Study and Corrosion Behaviour of Storage Materials in Different Blends of Palm Methyl Ester Biodiesel - Zainal, Mohd Hafiz (2018)
The trend to use green energy is becoming a custom in every country in the world. The advancement of technology has led us to reduce greenhouse gases production, conserve energy, and ultimately save our beautiful earth. Malaysia is also gearing towards the advancement, by implementing biodiesel blends across the country. We have been using up to B7 blend number which comprises of 7% of palm methyl ester and 93% of diesel. This project is dealing with the corrosion of storage materials when higher blends of Palm Methyl Ester (PME) Biodiesel fuels are introduced into the existing system, be it the car storage tank or even larger, bulkier tanks. The material used is mild carbon steel AISI 1080, aluminium AISI 6001, high density polyethylene (HDPE) and Teflon, studied under different blends of diesel; stock diesel, B5, B10, and B20. The test comprises of visual testing, microscopic evaluation, corrosion rate for metal, percentage mass change and hardness reduction. Corrosion rate of carbon steel at stock diesel is the highest compared to the other, achieving as high as 0.7093 mm/year. The increase in PME blend number has led to a decreasing corrosion rate of aluminium and increasing corrosion rate in carbon steel. The mass change percentage for Teflon and HDPE increases as PME blend number is increased. For Carbon steel, the mass change remains the same, while for aluminium, the mass change reduces as the blend number increases. The hardness of HDPE decreases as the blends increases, except for stock biodiesel, whilst the Teflon has shown increment in hardness reduction.